Green preparation and characterization of tentacle-like silver/copper nanoparticles for catalytic degradation of toxic chlorpyrifos in water. Issue 3 (June 2017) - Rosbero, Therese Marie S.; Camacho, Drexel H.
Graphical abstract: Highlights: Efficient co-reduction of Ag and Cu ions in Carica papaya extract. Unique star-shaped Ag/Cu bimetallic nanoparticle with tentacle-like structure. Nanocatalyst for degradation of chlorpyrifos pesticide in water. Green-synthesized bimetallic nanoparticles for treating water with pesticide contamination. Abstract: The synthesis of bimetallic nanoparticles is gaining attention due to a number of interesting and striking new properties that can be derived from the combination of two metals. In this study, bimetallic silver/copper (Ag/Cu) nanoparticles were prepared by co-reduction method using aqueous leaf extracts of Carica papaya as reducing agent. The synthesized nanoparticles showed a single UV–vis peak with a maximum absorption at 776 nm. The SEM and TEM images of bimetallic Ag/Cu nanoparticles displayed, among others, a unique star-like structure. HR-TEM mapping revealed uniform distribution of Ag & Cu forming a bimetallic nanoparticle. The bimetallic Ag/Cu has an average hydrodynamic particle size of 420.7 nm (DLS) and TEM size of ∼150 nm. The presence of elemental Ag, Cu, C, N and O was confirmed in EDX spectra suggesting nitrogen containing metabolites capping the bimetallic Ag/Cu nanoparticles. The XRD patterns of bimetallic Ag/Cu nanoparticles displayed crystallinity with observed diffraction peaks corresponding to Ag, Ag2 O and CuO. The synthesized bimetallic nanoparticles were then utilized for water purification application using the toxic pollutant, chlorpyrifos pesticide, as a model. Results showed that bimetallic Ag/Cu nanoparticles are efficient agents to promote degradation of chlorpyrifos in water, indicating the high potential of green synthesized nanometals for purifying water from pesticide contamination.